Perencanaan Ulang Tata Letak Fasilitas Pabrik Oncom Bu Nana Menggunakan Metode Activity Relationship Chart (ARC) dan Total Closeness Rating (TCR) - Haykal Heryawan; Putri Salbilah Taharoh; Maora Amelya Setiawan; Muhammad Rayhan Arrafii; Husnul Fikri (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to improve the effectiveness of facility arrangement at Pabrik Oncom Bu Nana by analyzing interactions among production activities and designing spatial layouts based on their priority levels. The current layout presents several critical issues, particularly because the equipment sanitation area is combined with the toilet, creating a significant risk of contamination and reducing hygiene during production. In addition, irregular material flow and excessive worker movement lead to inefficient work processes and may affect the quality of the final product. To address these issues, this study employs the Activity Relationship Chart (ARC) to evaluate the functional closeness among production areas, as well as the Total Closeness Rating (TCR) to determine facility placement priorities based on the intensity of inter-stage relationships. The results of the ARC analysis indicate that the fermentation room has the strongest link to the main stages of oncom production, requiring its placement to be closer to the preparation and molding areas. Findings from the TCR further emphasize that fermentation should become the primary focus in the layout redesign. Based on both methods, a more organized layout design is proposed by relocating the fermentation room to the beginning of the production flow, separating the toilet and sanitation room into two distinct areas, and restructuring the storage, molding, and drying spaces. This redesigned layout is expected to enhance cleanliness, improve material flow, and strengthen the operational effectiveness of Pabrik Oncom Bu Nana.